2021
DOI: 10.1016/j.jaad.2020.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Overview of TikTok's most viewed dermatologic content and assessment of its reliability

Abstract: Overview of TikTok's most viewed dermatologic content and assessment of its reliabilityTo the Editor: Around 80% of people seek medical information online, and #45% report that social media influences their decisions to seek medical care. 1,2 With [2 billion total downloads, TikTok is the world's fastest growing social media platform. This popular app allows users to create and share short videos on numerous topics, including health care. Previous studies have analyzed the dermatologic content posted on Instag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 1 publication
(1 reference statement)
1
41
0
2
Order By: Relevance
“…The methodology by which we identified these videos is described in our initial manuscript. 2 We previously reported that 96.8% (30/ 31) of these videos contained reliable educational content consistent with the American Academy of Dermatology guidelines, with a 50.1% greater probability of being reliable than videos posted by other content creators (P \ .00001). 2 In this follow-up study, we categorized these 31 videos according to their content and audiovisual features (Table II).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The methodology by which we identified these videos is described in our initial manuscript. 2 We previously reported that 96.8% (30/ 31) of these videos contained reliable educational content consistent with the American Academy of Dermatology guidelines, with a 50.1% greater probability of being reliable than videos posted by other content creators (P \ .00001). 2 In this follow-up study, we categorized these 31 videos according to their content and audiovisual features (Table II).…”
mentioning
confidence: 75%
“…To the Editor: We thank Zheng et al 1 for their interest in our manuscript, ''Overview of TikTok's most viewed dermatologic content and assessment of its reliability.'' 2 We agree that TikTok holds great potential as a platform for disseminating educational information. To put this potential into perspective, the number of views for the hashtag #acne on TikTok more than doubled from 3.0 to 6.7 billion in just the past 5 months (Table I).…”
mentioning
confidence: 89%
“…Although TikTok is relatively new, it has gained incredible popularity and has now over 689 million monthly active users [ 1 ]. With more than 2 billion total downloads since its debut, TikTok is the world’s fastest growing social media platform [ 22 ]. TikTok began as an app to create short comedy videos and dance clips, but as beauty tutorials and product demonstrations soon proved popular, so too did a professional opinion.…”
Section: Discussionmentioning
confidence: 99%
“…Other popular TikTok hashtags include #eczema, #psoriasis, and #hidradenitissuppurativa [ 42 ]. Content creators have been identified as patients, board-certified dermatologists, and estheticians, discussing everything from medically accurate educational videos to natural remedies attempted at home [ 44 ]. Several board-certified dermatologists now use TikTok in an effort to spread medically accurate information and dispel misinformation being shared by other users [ 42 ].…”
Section: Tiktok and Dermatologymentioning
confidence: 99%